2021
DOI: 10.1093/molbev/msab091
|View full text |Cite
|
Sign up to set email alerts
|

Piggybacking on Niche Adaptation Improves the Maintenance of Multidrug-Resistance Plasmids

Abstract: The persistence of plasmids in bacterial populations represents a puzzling evolutionary problem with serious clinical implications due to their role in the ongoing antibiotic resistance crisis. Recently, major advancements have been made towards resolving this “plasmid paradox” but mainly in a non-clinical context. Here we propose an additional explanation for the maintenance of multidrug resistance (MDR) plasmids in clinical Escherichia coli strains. After co-evolving two MDR plasmids encoding last resort car… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 85 publications
3
28
1
Order By: Relevance
“…As a consequence, small mutations—in some cases just single base changes—can be sufficient to ameliorate even a very large plasmid with hundreds of genes. Previous studies have tended to focus on smaller, nonconjugative replicons [ 25 , 30 , 67 ], or have identified plasmid compensatory mutations with substantial pleiotropic effects: disruption or deletion of conjugative machinery from the plasmid (rendering it immobile) [ 28 , 68 ]; deletion of large portions of the plasmid [ 34 , 69 ]; or disruption of extensive and multifunctional regulatory circuits [ 31 , 33 , 70 ]. In contrast, our data show that single mutations can enable large, natural, conjugative, plasmids to become rapidly accommodated with few obvious trade-offs, and furthermore begins to describe the molecular negotiation by which this occurs ( Fig 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, small mutations—in some cases just single base changes—can be sufficient to ameliorate even a very large plasmid with hundreds of genes. Previous studies have tended to focus on smaller, nonconjugative replicons [ 25 , 30 , 67 ], or have identified plasmid compensatory mutations with substantial pleiotropic effects: disruption or deletion of conjugative machinery from the plasmid (rendering it immobile) [ 28 , 68 ]; deletion of large portions of the plasmid [ 34 , 69 ]; or disruption of extensive and multifunctional regulatory circuits [ 31 , 33 , 70 ]. In contrast, our data show that single mutations can enable large, natural, conjugative, plasmids to become rapidly accommodated with few obvious trade-offs, and furthermore begins to describe the molecular negotiation by which this occurs ( Fig 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have tended to focus on smaller, non-conjugative replicons [25,30,64], or have identified plasmid compensatory mutations with substantial pleiotropic effects: disruption or deletion of conjugative machinery from the plasmid (rendering it immobile) [28,65]; deletion of large portions of the plasmid [34,66]; or disruption of extensive and multi-functional regulatory circuits [31,33,67]. In contrast, our data shows that single mutations can enable large, natural, conjugative, plasmids to become rapidly accommodated with few obvious tradeoffs, and furthermore describes the molecular negotiation by which this occurs (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We show that PFLU4242 expression is induced by a global regulator of secondary metabolism, the GacA/S two-component system, and so our data is consistent with the hypothesis that disruption to GacA/S could exert its effect through repression of PFLU4242. It is possible that global regulators have been implicated in plasmid persistance due to their regulatory effects on more proximal causes of plasmid conflict [31,67]. The combined size of the gacA and gacS genes (~3.4 kb) is over twice that of PFLU4242 (~1.6 kb) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It was thought that ARGs would impose a fitness cost, and thus at antimicrobial concentrations below the MSC-resistant bacteria carrying the ARG would be outcompeted by non-resistant bacteria. However, recent evidence suggests that several ARGs may impose a low fitness cost, be cost free (sometimes involving development of compensatory mechanisms), or in some cases confer a fitness benefit (Andersson and Hughes, 2010;Li et al, 2020;Kloos et al, 2021;Pietsch et al, 2021). Consequently, ARBs may persist within microbial communities for a duration related to the fitness cost of AMR and general ability to compete with other microorganisms, in some cases decreasing over time and in others persisting, or actually increasing, even in the absence of antimicrobial selection (Li et al, 2020;Perrin-Guyomard et al, 2020;Kloos et al, 2021).…”
Section: 4mentioning
confidence: 99%
“…However, recent evidence suggests that several ARGs may impose a low fitness cost, be cost free (sometimes involving development of compensatory mechanisms), or in some cases confer a fitness benefit (Andersson and Hughes, 2010;Li et al, 2020;Kloos et al, 2021;Pietsch et al, 2021). Consequently, ARBs may persist within microbial communities for a duration related to the fitness cost of AMR and general ability to compete with other microorganisms, in some cases decreasing over time and in others persisting, or actually increasing, even in the absence of antimicrobial selection (Li et al, 2020;Perrin-Guyomard et al, 2020;Kloos et al, 2021). The interaction of environmental antimicrobial residues and microbial communities will not be dealt with in detail in this scientific opinion.…”
Section: 4mentioning
confidence: 99%